Are the player selection process and performance influenced by relative age effect in elite women's handball? - de la Rubia, A.; Lorenzo-Calvo, J.; Rivilla-García, J.; Marquina, M. (Journal of Human Kinetics, 2021)
The relative age effect (RAE) is a phenomenon present in team sports, but it does not influence each gender to the same extent. This study aimed to examine the RAE and its relation to performance in international women's handball competitions (2017/18 World Championships). The sample was composed of 1,096 female players distributed into three categories: youth or under 18 (n = 369); junior or under 20 (n = 328) and senior (n = 399). The teams were divided into four groups based on their final position (medalist, quarter-finalist, eight-finalist and bottom-eight teams). The birthdate distribution (trimesters and semesters) was analysed according to the competition category and the playing position. Differences between the expected and observed birthdate distribution were checked using the chisquare statistical test followed by the calculation of the odds ratio. The results revealed, by trimester, the presence of the RAE in the youth (x2(7) = 87.22; p < 0.001) and junior (x2 (7) = 33.12; p < 0.001) categories, with no impact on senior (p > 0.05). The effect size was relatively strong in the youth category (Vc = 0.48). By semester, the prevalence of the RAE was also found in the senior category (p < 0.05). According to the playing position, the RAE was especially detected in `goalkeeper` (p < 0.01) and `centre-back` (p < 0.05) positions, both in U-18 and U-20 categories. Surprisingly, this effect also appeared in the `back` players in the senior category (p < 0.05). A prevalence of the RAE was identified in teams with a higher final position, but interestingly had a greater impact in the quarter-finalist teams (p < 0.001) than in the medalist teams (p < 0.01). The findings demonstrated that the RAE tends to decrease as the chronological age of players increases, demonstrating a strong presence according to collective performance in international women`s handball.